LEGAL CONSEQUENCES OF BANKRUPTCY DECISIONS AGAINST PT. ASURANSI JIWA KRESNA (STUDY OF THE SUPREME COURT DECISION NUMBER: 647 K/PDT.SUS-BANKRUPTCY/2021) - Alum Simbolon; Cindy Leowardy (Journal Equity of Law and Governance, 2024)
Abstract. The purpose of this thesis research conducted by researchers with the title Legal Consequences of Bankruptcy Decisions Against PT Asuransi Jiwa Kresna (Study of Supreme Court Decision Number 647 K/Pdt.Sus-Bankruptcy/2021) is aimed at knowing and understanding the legal consequences of a bankruptcy decision against an insurance company that has an impact on customers and on the company itself. The research result of this thesis research is that the bankruptcy experienced by PT Asuransi Jiwa Kresna will further complicate the position of customers to receive their benefits because in bankruptcy, the company has no authority over its assets and the authority to manage these assets will be transferred to the curator. Generally, curators need a long time to be able to liquidate bankruptcy assets. In addition, after liquidation, the liquidation proceeds will be reduced by several costs such as curator fees and taxes. Therefore, the percentage of customer's income will be less. As a form of responsibility, debtors can submit a Financial Restructuring Plan (RPK) to OJK as a step to fulfill their obligations.